The Relationship Between Anemia in Maternity and Prematurity at the Balaraja Community Health Center - Susilowati, Lilik (JOURNAL EDUCATIONAL OF NURSING(JEN), 2023)
The aim of this study was to determine the relationship between anemia in mothers giving birth and prematurity. The research method used a cross sectional approach using secondary data based on medical records of mothers giving birth at the Balaraja health center, which met the inclusion criteria of 735 people. The data is presented in a frequency distribution table and cross table, then the chi squre test is used. The results of this study show that based on maternal characteristics, 78.5% were aged 20-34 years, 68.8% were primiparas, 59.3% had ≥ 4 ANC visits, 8.6% had a high prevalence of moderate anemia, and 8.6% had a severe anemia. as much as 0.5%. The prevalence of prematurity is 7.76%. The relationship between anemia in mothers giving birth and prematurity is statistically significant (p<0.05). Relative risk (RR) of mild anemia with prematurity 1.47; RR of moderate anemia with prematurity 3.45; and RR of severe anemia with prematurity 18. The conclusion of this study is that the relationship between anemia in mothers giving birth and prematurity is statistically significant (p < 0.05).